The role of calcium metabolism disorders in induction of hypersensitivity in cardiovascular diseases - N. S. Deeva; A. V. Shabaldin; L. V. Antonova (Бюллетень сибирской медицины, 2021)
Impairment of extracellular and intracellular calcium homeostasis can have a damaging effect on the functioning of both individual organs and systems and the whole organism. In the cardiovascular system, disorders ofcalcium metabolism trigger a cascade of auto-inflammatory responses, leading to persistent morphological and functional disturbances. In this review, impaired calcium homeostasis is defined as a predictor of the development of hypersensitivity in cardiovascular diseases. We analyzed the development of a cardiovascular pathology (atherosclerosis, aortic valve calcification, and essential hypertension) with impaired calcium metabolism and pathological mechanisms that cause the disturbances. Calcium sensors, polymorphic variants of genes, and hormones involved in calcium metabolism can reveal the features of calcium metabolism and contribute to a personalized approach to treatment of cardiovascular diseases.